Assessment of physical work demand of short distance industrial gas delivery truck drivers. (November 2020) - Sekkay, Firdaous; Imbeau, Daniel; Dubé, Philippe-Antoine; Chinniah, Yuvin; de Marcellis-Warin, Nathalie; Beauregard, Nancy; Trépanier, Martin
Abstract: Aim: This study assessed the work-related physical demands of short-distance truck drivers employed by a large gas delivery company in Canada. Methods: A total of 19 truck drivers participated in the data collection, which included a combination of self-reports, field observations and direct measurements to report on the work shift task composition, postures, physical workload, and force exertions. Results: Driving (mean of 43% of daily work shift) and delivering gas cylinders to customers (28%) were the main tasks of the truck drivers. Delivering gas cylinders measured as moderate level work and daily work duration was not excessive with respect to mean cardiac strain for most drivers. However, manual handling and force exertion activities were frequent and deemed unsafe most of the time with respect to existing guidelines on manual materials handling. Conclusion: This study documents physical risk factors that are consistent with musculoskeletal pain prevalence reported for short-distance truck drivers. Highlights: Short-distancetruck drivers had group mean fitness (MWC) that was average compared to their age group of Canadian male workers. Driving and delivering gas cylinders to customers were the main tasks of the daily work of short-distance truck drivers. The daily overall workload was not excessive given the shift duration, and delivering gas cylinders was assessed as moderate work.. Manual handling activities were frequent and deemed unsafe most of the time with respect to existing guidelines on manual handling. Awkward postures were often adopted during manual handling activities and force exertions.